PEMBUATAN DAN KARAKTERISASI KARBON AKTIF MONOLIT DARI KAYU KARET DENGAN VARIASI KONSENTRASI KOH UNTUK APLIKASI SUPERKAPASITOR - Inrizky Domy Muchammadsam; Erman Taer; Rakhmawati Farma (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
Development of monolithic carbon electrodes with a combination of physical and chemical activation process can improve performance of cell supercapacitor. Monolithic carbon electrodes were made from rubber wood cross-section of the printed form of pellets, then were carbonized at temperature of 600ºC in N2 gas atmosphere and followed by physical activation process at 900ºC for 2 hours in a CO2 gas atmosphere. KOH of 1 and 5 M and HNO3 of 25% solutions were used as of the chemical activation in order to activate functional groups. Characterization of electrochemical supercapacitor cell utilized two-electrode of cyclic voltammetry with 1 M H2SO4 solution was used as electrolyte. Scanning electron microscope and X-ray diffraction were carried out to study the structure of surface morphology and crystalline properties of monolithic carbon electrodes. Specific capacitance for electrodes 1 M KOH and 5 M KOH was obtained as high as 71.08 and 115.38 F/g respectively. These results indicate that increasing the concentration of KOH can improve the performance of the electrode supercapacitor cells.